Tratamiento de menopausia con acupuntura vs fitofármacos y placebo - García Esparza, Ixchel; Castellanos López, Eduardo Alberto; Castellón Berumen, Martha Lorena (Universidad Autónoma Metropolitana, 2005)
OBJECTIVE: To evaluate the effectiveness of the Acupuncture in the treatment of the menopause. To evaluate the effectiveness of the Soy Isoflavones in the treatment of the menopause. To compare the benefits of both against the placebo effect in the treatment of the Climatéric syndrome MATERIAL AND METHODS: A study comparative, open, observational, prospective and longitudinal of a sample of 115 patients with menopause that went to the clinic of acupuncture of the UAM-Iztapalapa, DF. Mexico with ages between 45 and 65 years old. They were distributed in random form in three study groups, A) 37 for treatment with Acupuncture, abandoning the study 5 pacientes;B) 48 under treatment Soy Isoflavones abandoning the study 8 patients and C) 30 with sham acupuncture - they abandoned the study 11 patients. . We measured the Climateric symptoms since the beginning till the end of the experiment with Kupperman Index.. Group A were programmed to receive 10 sessions, 2 times per week. In the Soy Isoflavones group they were provided a daily dose of 50 mg by 35 days. For the placebo group they were carried out similar sessions to the acupuncture group RESULTS: as for the realized ANDEVA to the index of Kupperman with the final data, significant differences exist among the treatments (P < 0.001) (SS=1,887.45); g.l. = 2.85; M.S. = 943.72; F=17.39). When using the securities average of the indexes of Kupperman for treatment, the variance analysis shows us that significant differences exist (P=0.007) (SS=377.73; g.l. = 2.85; M.S. =188.86; F=5.25), but this it is given between the acupuncture treatment and the placebo (P=0.005), It didn't seize with that of isoflavonas (P=0.187), and the isoflavonas treatments and the placebo (P=0.178). The final result of the treatments points out that each one is different one of another in a significant way CONCLUSIONS: Of the obtained results we finishes categorical way that so much the therapy with the help of acupuncture like the therapy with the help of Soy isoflavones are an important and effective option for the treatment of the Climateric syndrome symptomatology, offering the first better results and goods adverse minima or null. The Chinese traditional medicine when trying to the organism according to the diagnosed syndrome, with the acupuncture, offers an integral improvement which is not achieved with the Soy isoflavones that only improve the hot flashes via binding alfa and beta estrogen receptors.; OBJETIVO: Evaluar la eficacia de la Acupuntura en el tratamiento de la menopausia. Evaluar la eficacia de las Isoflavonas de soya en el tratamiento de la menopausia. Comparar los efectos de ambas contra el efecto placebo en el tratamiento del síndrome climatérico MATERIAL Y MÉTODOS: Estudio comparativo, abierto, observacional, prospectivo y longitudinal de una muestra de 115 pacientes con menopausia que acudieron a la clínica de acupuntura de la UAM-Iztapalapa, DF. México con edades entre 45 y 65 años. Se distribuyeron en forma aleatoria en tres grupos de estudio, A) 37 para tratamiento con Acupuntura, abandonando el estudio 5 pacientes;B) 48 para tratamiento a base de Isoflavonas abandonando el estudio 8 pacientes y C) 30 con acupuntura- placebo, abandonaron el estudio 11 pacientes. .Se llevo a cabo la medición de la sintomatologia tanto al inicio como a lo largo del experimento mediante la ayuda del índice de Kupperman. Del grupo de A, se programaron 10 sesiones de 2 veces por semana. En el grupo de Isoflavonas se les proporcionó una dosis diaria de 50 mg por 35 dias. Para el grupo de placebo se realizaron sesiones similares al grupo de acupuntura RESULTADOS: En cuanto al ANDEVA realizado al índice de Kupperman con los datos finales, existen diferencias significativas entre los tratamientos (P< 0.001) (SS=1,887.45); g.l.=2.85; M.S.= 943.72; F=17.39). Al utilizar los valores promedio de los índices de Kupperman por tratamiento, el análisis de varianza nos muestra que existen diferencias significativas (P=0.007) (SS=377.73; g.l.=2.85; M.S.=188.86; F=5.25), pero esta se da entre el tratamiento de acupuntura y el placebo (P=0.005), no así con el de isoflavonas (P=0.187), y los tratamientos de isoflavonas y el placebo (P=0.178). El resultado final de los tratamientos señala que cada uno es diferente uno de otro de manera significativa CONCLUSIONES: De los resultados obtenidos se concluye de manera categórica que tanto la terapia a base de acupuntura como la terapia a base de isoflavonas de soya son una opción importante y efectiva para el tratamiento de la sintomatología del síndrome climatérico, ofreciendo la primera mejores resultados y efectos adversos mínimos o nulos. La medicina tradicional china al tratar al organismo de acuerdo al síndrome diagnosticado, con la acupuntura, ofrece una mejoría integral la cual no se logra con las isoflavonas de soya que solamente mejoran la sintomatología vasomotora ligandose a receptores alfa y beta estrogénicos.